Rijksmuseum Amsterdam; paintings. - Faggin, Giorgio; Ruggeri, Ugo.; Monti, Raffaele; Rijksmuseum (Netherlands) (New York, Newsweek, 1969)
(Great Museums of the World). Includes bibliographical references and index.
Keywords: Painting -- Netherlands -- Amsterdam -- Catalogs